O diagnóstico da organização dos processos de trabalho utilizando os critérios ergonômicos-sociotécnicos, adequação e econômicos: ferramenta para a tomada de decisão gerencial - Barros, Maria Helena Bessa (2009)
This study aims at proposing a diagnostic method of organization of work processes using sociotechnical ergonomics criteria (comfort and efficiency), suitability (usability and security) and economic (cost-benefit and cost-effectiveness) for management decision making. The proposed tool aims at articulating in its scope the humanistic approach whose focus is on the Human Factors skills and competence, and economical approach that seeks production efficiency. Such proposal results from the finding that although there has been evolution and development of organizational practices, production systems employed by the contemporary industry include in their configuration both the rationalization of work and the techniques and current methods of production management, which incorporate technology, knowledge and innovation. The use of ergonomic criteria is justified on the consideration of how work processes are organized to ensure the sustainability of the organization in the long run. The methodology of this research was a survey. The research universe is characterized by the organization of production processes of a unit of agribusiness in the dairy segment located in the region of Campos Gerais. The proposed model consists of nine steps in a structured conceptual model organized and systematized in order way to verify the correlation between the data of the analysis considered the reality of the organizational context studied. The units of analysis studied refer to the components of the overall organization and work process and ergonomic criteria. The application of this study allowed us to extend the classical view of the ergonomic analysis and methods of analysis when detecting problems, discern the harmful factors to the work and workers to ensure continuous improvement of processes. The methodological validation of this tool is configured as an increase in the administrative models governing the productive sector by incorporating and integrating two distinct approaches to its scope, which are experienced separately by the organization: the health and efficiency of processes. The diagnosis human and productive factors integration regarding the organization of work processes enabled us to understand the complexity of the reality of the work being investigated. From these findings it is inferred that Ergonomics is articulated and contextualized with the production system, contributing to the organizational development as a whole.